Design And Development Of Programming Learning Platform Based On Heuristic Approach In Assessment Module With Iterative And Incremental Method (case Study: Information System Telkom University) - Dewansyah Adi Saputra; Soni Fajar Surya Gumilang; Muhammad Azani Hasibuan (eProceedings of Engineering, 2015)
Abstract — In general  programming learning  system there  should be a process of measurement. However, acommon  measurement process are still many shortcomings  and the high level of fraud. So the measurement is not accurate and  also there  are  absence of a continuous  learning  process. The  research   aims  to  develop  a  platform   learning   based  on  heuristic   approach  focussed  on assessment  module  especially in programming algorithm  course.  This module  used to measure  a student's ability more accurately and it will be part  of a heuristic  based learning  process. For this platform development,  it will use iterative  and  incremental methodology.  By using  the  learning platform, lecturer and  student  can  joy experience  learn  programming algorithm  with  attractive course.  Index Terms— e-learning,  platform  learning,  assessment, iterative and incremental